The E3 ubiquitin ligase DESYNAPSIS1 regulates synapsis and recombination in rice meiosis - Lijun Ren (Elsevier, 2021)
Summary: Synaptonemal complex (SC) assembly and homologous recombination, the most critical events during prophase I, are the prerequisite for faithful meiotic chromosome segregation. However, the underlying regulatory mechanism remains largely unknown. Here, we reveal that a functional RING finger E3 ubiquitin ligase, DESYNAPSIS1 (DSNP1), plays significant roles in SC assembly and homologous recombination during rice meiosis. In the dsnp1 mutant, homologous synapsis is discontinuous and aberrant SC-like polycomplexes occur independent of coaligned homologous chromosomes. Accompanying the decreased foci of HEI10, ZIP4, and MER3 on meiotic chromosomes, the number of crossovers (COs) decreases dramatically in dsnp1 meiocytes. Furthermore, the absence of central elements largely restores the localization of non-ZEP1 ZMM proteins and the number of COs in the dsnp1 background. Collectively, DSNP1 stabilizes the canonical tripartite SC structure along paired homologous chromosomes and further promotes the formation of COs.